Humanistic Approaches in Learning Arabic to Increase Motivation of Students' Learning: Pendekatan Humanistik dalam Pembelajaran Bahasa Arab Upaya Meningkatkan Motivasi Belajar Siswa - Dudung Hamdun; Nurul Islam (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2023)
This study aims to determine how the implementation of the humanistic approach in learning Arabic and to determine its effect on increasing student learning motivation. The applied humanistic approach adopts the principles of Gestalt theory. i.e., humanistic teachers believe that students will be motivated to study teaching materials if they are related to their needs and wants; educational goals should encourage students' desire to learn; humanistic educators believe that grades are irrelevant and only self-evaluation is meaningful; do not separate cognitive and affective domains; and learn without threat. The results show that the implementation of the humanistic approach in Arabic language learning is in accordance with the principles of Gestalt. The implementation of the humanistic approach in Arabic language learning is also able to increase students' learning motivation. This can be seen from the statistical significance value (2-tailed) of 0.000 <0.05 between the pre-test and post-test results, which means there is a significant difference. These results can be concluded that through the implementation of a humanistic approach to learning Arabic can increase student motivation. So that the alternative hypothesis, which states that the implementation of a humanistic approach in learning Arabic can increase the learning motivation of students in class X IPA 1 is proven or accepted,. Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana implementasi pendekatan humanistik dalam pembelajaran bahasa arab dan untuk mengetahui pengaruhnya terhadap peningkatan motivasi belajar siswa. Pendektan humanistik yang diterapkan mengadopsi prinsip teori Gestalt. yaitu guru yang humanis percaya bahwa siswa akan termotivasi untuk mengkaji bahan ajar jika terkait dengan kebutuhan dan keinginannya; tujuan pendidikan harus mendorong keinginan siswa untuk belajar; pendidik yang humanis percaya bahwa nilai tidak relevan dan hanya evaluasi diri yang bermakna; tidak memisahkan domain kognitif dan afektif; dan belajar tanpa ancaman. Hasil penelitian menunjukkan bahwa implementasi pendekatan humanistik dalam pembelajaran bahasa Arab sudah sesuai dengan prinsip-prinsip Gestalt. Penerapan pendekatan humanistik dalam pembelajaran bahasa Arab juga mampu meningkatkan motivasi belajar siswa. Hal ini terlihat dari nilai statistik signifikansi (2-tailed) sebesar 0,000 < 0,05 antara hasil pre-test dan post-test yang berarti terdapat perbedaan yang signifikan. Hasil ini dapat disimpulkan bahwa melalui implementasi pendekatan humanistik dalam pembelajaran bahasa Arab dapat meningkatkan motivasi belajar siswa. Sehingga hipotesis alternatif yang menyatakan implementasi pendekatan humanistik dalam pembelajaran bahasa Arab dapat meningkatkan motivasi belajar siswa kelas X IPA 1 terbukti atau diterima.